How do integrative practices influence patient-centered care?: An exploratory study comparing diabetes and mental health care. Issue 2 (April 2016) - Novikov, Zhanna; Glover, Wiljeana J.; Trepman, Paula C.; Naveh, Eitan; Goldfracht, Margalit
Abstract : Background: Integration between organizational units to achieve common goals has been of interest to health systems because of the potential to improve patient-centered care. However, the means by which integrative practices actually influence patient-centered care remain unclear. Whereas many studies claim a positive association between implementation of integrative practices and patient-centered care, others raise concerns that integrative practices may not necessarily improve patient-centered care. Purpose: The aim of this study was to explore the mechanism by which integrative practices influence patient-centered care and to suggest a systematic approach for effective integration. Approach: We conducted a qualitative study comparing diabetes and mental health services through focus groups with 60 staff members from one health maintenance organization. We developed quantitative indicators to support the suggested model. Findings: We identified a five-category framework of integrative practices that each directly and distinctively influences patient-centered care. Moreover, our findings suggest that integrative practices influence patient-centered care indirectly through creation of interdependent treatment competence, which enables providers to repeatedly deliver interdependent treatment in a flexible and adaptive way. Practical Implications: Providers should carefully implement integrative practices considering patient and disease characteristics, as our findings suggest that more implementation of integrative practices is not necessarily better for patient-centered care. Specifically, optimal implementation refers to the collective implementation of different integrative practices and thus encompasses both the extent (i.e., the amount of currently implemented practices out of those considered important to implement) and the extensiveness (i.e., the amount relative to the implementation of other practices) that may lead to interdependent treatment competence and higher patient-centered care. We suggest a creative measurement method of comparing the relative implementation of integrative practices that may assist managers and policy makers in developing interdependent treatment competence.